Experimental evaluation of Haplosporidium pinnae DNA detection and degradation under semi-controlled conditions - PAVLINEC, ŽELJKO; CATANESE, GAETANO; MIČIĆ, MILENA (Mediterranean Marine Science, 2025)
The fan mussel Pinna nobilis is one of the most endangered marine species in the Mediterranean Sea, having suffered mass mortality events driven primarily by the haplosporidian parasite Haplosporidium pinnae. To support the conservation of this critically endangered bivalve, the development of reliable, non-invasive detection methods is essential. Here, we tested the persistence of H. pinnae DNA in seawater under semi-controlled aquarium conditions through two filtration experiments. In the first experiment, seawater was enriched with parasite DNA from a live infected individual prior to its removal, whereas in the second experiment, enrichment included post-mortem release. Water samples were collected over several weeks and tested using end-point PCR and real time PCR assays targeting H. pinnae. Parasite DNA was detectable for up to 18 days in the live-infected experiment and 15 days in the post-mortem experiment. Detection success depended strongly on amplicon size, with shorter fragments persisting longer than larger ones. Real-time PCR also revealed different degradation dynamics between the two experiments, suggesting variation in the initial DNA load and release mechanisms. These results provide an empirical baseline for understanding the persistence of H. pinnae DNA in seawater. Although environmental variability in open waters may shorten detection windows, our findings demonstrate that eDNA remains detectable long enough to inform monitoring efforts. From a conservation perspective, eDNA assays could help identify H. pinnae-free refugia and support proactive strategies for safeguarding surviving populations of P. nobilis across the Mediterranean.